Tissue-specific codon usage and the expression of human genes - Plotkin, Joshua B. (National Academy of Sciences, 2004)
A diverse array of mechanisms regulate tissue-specific protein levels. Most research, however, has focused on the role of transcriptional regulation. Here we report systematic differences in synonymous codon usage between genes selectively expressed in six adult human tissues. Furthermore, we show that the codon usage of brain-specific genes has been selectively preserved throughout the evolution of human and mouse from their common ancestor. Our findings suggest that codon-mediated translational control may play an important role in the differentiation and regulation of tissue-specific gene products in humans.